2004
DOI: 10.1152/ajpheart.00741.2003
|View full text |Cite
|
Sign up to set email alerts
|

Transcription activator protein 1 mediates α- but not β-adrenergic hypertrophic growth responses in adult cardiomyocytes

Abstract: .-In some models of cardiac hypertrophy, activation of activator protein 1 (AP-1) correlates with growth. However, AP-1 is also activated by stimuli not involved in cardiac growth. This raises the following questions: does AP-1 plays a causal role for cardiomyocyte growth, and is this role model or stimulus dependent? We used a single model to address these questions, i.e., ventricular cardiomyocytes of adult rats, and two growth stimuli, i.e., ␣-and ␤-adrenoceptor agonists [10 M phenylephrine (PE) and 1 M iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 29 publications
2
37
0
4
Order By: Relevance
“…Our finding that the stimulation of α 1 -and β-adrenoceptors causes activation of NFκB and AP-1 in the venom gland is in line with several studies that show that the stimulation of α-and β-adrenoceptors induces c-fos expression in a variety of cells, including cardiac myocytes, vascular smooth muscle cells, neuroblastoma cells, brown adipocytes and hepatocytes (Iwaki et al, 1990;Shilling et al, 1991;Okazaki et al, 1994;Thonberg et al, 1994;GarciaSáinz and Alcántara-Hernández, 1996;Im et al, 1998;Taimor et al, 2004). All α-adrenoceptor subtypes were able to induce the expression of c-fos and c-jun, and this effect seems to be mediated by PKC, but α 1 -adrenoceptor subtypes vary in the efficacy of this induction (García-Saínz et al, 1998).…”
Section: Discussionsupporting
confidence: 80%
“…Our finding that the stimulation of α 1 -and β-adrenoceptors causes activation of NFκB and AP-1 in the venom gland is in line with several studies that show that the stimulation of α-and β-adrenoceptors induces c-fos expression in a variety of cells, including cardiac myocytes, vascular smooth muscle cells, neuroblastoma cells, brown adipocytes and hepatocytes (Iwaki et al, 1990;Shilling et al, 1991;Okazaki et al, 1994;Thonberg et al, 1994;GarciaSáinz and Alcántara-Hernández, 1996;Im et al, 1998;Taimor et al, 2004). All α-adrenoceptor subtypes were able to induce the expression of c-fos and c-jun, and this effect seems to be mediated by PKC, but α 1 -adrenoceptor subtypes vary in the efficacy of this induction (García-Saínz et al, 1998).…”
Section: Discussionsupporting
confidence: 80%
“…CRE- decoy oligonucleotides may provide a powerful new means of combating cancers, and other pathological conditions by regulating the expression of cAMP-responsive genes (25). Phenylephrine stimulated DNA binding activity of AP-1 and increased protein synthesis in cardiomyocytes of adult rats, and inhibition of AP-1 binding activity by CRE-decoy oligonucleotides abolished both of these growth responses (57). In another study, the CRE-decoy oligonucleotide treatment was shown to inhibit ovarian cancer cell growth and caused a marked reduction in MMP-9 activity (58).…”
Section: Discussionmentioning
confidence: 99%
“…E.g., NFAT3, MEF-2 and GATA-4 have been reported to play a role in cardiac hypertrophy [18,19]. Moreover, fos and jun, known substrates of calpain 1 and 2 [20], can act as causal mediators of hypertrophic growth of cardiomyocytes [21,22]. The search of substrates for calpain 9, especially in heart and kidney as target organs, may be a key activity in order to understand the mode of action of this calpain isoform in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%